An Exploration of the Possibility for Establishing Reverse Innovation through Strategic Alliance in Emerging Markets - Jia, Xiaodi (2018)
The field of reverse innovation has been received tremendous interest in the business environment. However, in spite of the wealth of work on the risks and opportunities of reverse innovation, there was little insight into what approaches are applicable for carrying out reverse innovation in emerging markets. The objective of this dissertation is to highlight the increasing importance of reverse innovation and examine the possibility for carrying out reverse innovation through strategic alliance. We first characterize the very nature of reverse innovation and identify the essential factors required in the process of reverse innovation. These elements are further applied to analysis the case study of the dissertation, which introduced a success example of reverse innovation in India. The findings indicate that reverse innovation is beneficial for MNEs who want to win in emerging markets and it is in fact possible for reverse innovation to be carried out through effective strategic alliance strategy, under certain circumstances. Local-growth teams play a crucial role in this process. The dissertation provides important implications for theory of global innovation and emerging economies.